Pemberdayaan Komunitas Wali Murid TK Dharma Wanita Berbasis Olahan Krupuk Puli Dan Umbi Talas Desa Sukosari Kecamatan Kabupaten Jember - Abdul Mun'im (Al-Ijtimā': Jurnal Pengabdian Kepada Masyarakat, 2021)
Comunity, the guardian of the pupils of TK Dharma Wanita, is a society in Suksari Village, Jember Regency, under the aegis of the TK Dharma Wanita institution. Which has potential assets in the form of raw puli chips in the group and some members also have assets in agricultural products, namely taro tubers, both of which still have the potential to grow into processed products that can independently increase the economy of the member. The impact of empowerment using the Asset Based Community Development (ABCD) approach in the Dharma Wanita TK Dharma Wanita Guardian Community. The growth of community assets dependent on the production of crackers and taro tubers in the Dharma Wanita TK Dharma Female Guardians community has a major impact on the improvement of the member economy, as this can be seen in increasing the economic value of community-owned assets, namely puli crackers and taro tubers Keyword: Development, Community, Econmic Krupuk Puli and Talas.